1994
DOI: 10.1017/s0003356100007169
|View full text |Cite
|
Sign up to set email alerts
|

Fish-meal supplement for severely undernourished ewes: effects on apparent digestibility and utilization of the diet

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0003356100007169How to cite this article: P. Kabré and M. Petit (1994). Fish-meal supplement for severely undernourished ewes: effects on apparent digestibility and utilization of the diet. AbstractEight non-pregnant, non-lactating adult ewes weighing 56 kg were fed for 26 days on a meadow hay (organic matter 937 g, crude protein 107 g, metabolizable energy (ME) 8-3 M] per kg dry matter) to satisfy half of their daily energy and protein maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Galbraith et al (1997) observed higher levels of NEFA for the unsupplemented treatment compared to fish meal supplementation. Kabré and Petit (1994) found NEFA levels of approximately 1.1 AEq/100 ml plasma for both supplemented and unsupplemented lambs, which would correspond to the values observed for treatment CON in the present experiment. However, the feed restriction period in that study was longer, and experimental lambs where in medium body condition at the beginning of that study.…”
Section: Metabolitessupporting
confidence: 88%
See 4 more Smart Citations
“…Galbraith et al (1997) observed higher levels of NEFA for the unsupplemented treatment compared to fish meal supplementation. Kabré and Petit (1994) found NEFA levels of approximately 1.1 AEq/100 ml plasma for both supplemented and unsupplemented lambs, which would correspond to the values observed for treatment CON in the present experiment. However, the feed restriction period in that study was longer, and experimental lambs where in medium body condition at the beginning of that study.…”
Section: Metabolitessupporting
confidence: 88%
“…1C), which are about 50% higher than values reported by Kabré and Petit (1994) for ewes in negative energy balance. Diet SFM produced the numerically highest levels.…”
Section: Non-esterified Fatty Acids (Nefa)mentioning
confidence: 55%
See 3 more Smart Citations